A multi-site study of emerging adults in collegiate recovery programs at public institutions. (June 2021) - Hennessy, Emily A.; Tanner-Smith, Emily E.; Nichols, Lindsey M.; Brown, Tiffany B.; Mcculloch, Bryce J.
Abstract: Background: Collegiate Recovery Programs (CRPs) are campus-based support programs for substance use and recovery needs among college students. These CRPs utilize a variety of program activities and components aimed at promoting healthy development and sobriety while encouraging college retention among participants. Objectives: Describe the types of activities and administrative structures used in CRPs, examine the characteristics of students involved in this sample, and explore changes in students' outcomes after they have enrolled in a CRP. Methods: This multi-site study collected de-identified data from six CRPs on participating students' sociodemographic characteristics, academic performance, substance use, and socioemotional well-being. One CRP administrator from each participating site completed a survey on CRP programming. Data were harmonized across sites and descriptively summarized. Results: Participating CRPs had been in operation since 2007 to 2012. Five of the six sites provided individual-level student data for a total of 861 students (56% male, 89% White, 91% undergraduate). Student histories indicated the majority had received treatment for a substance use disorder (82%) or mental health concern (77%), 56% had criminal justice involvement, and the majority were in recovery less than five years. Student GPA improved in three of the four sites that provided student GPA data. Conclusions: CRPs collect diverse types of data on participating students, but more effort is needed to focus on systematic data collection. Findings from this study suggest that CRPs play an important role in providing needed services for this vulnerable population of college students. Highlights: Program level data were collected from six collegiate recovery programs (CRPs). Five of these CRPs provided de-identified student data representing 861 students. 82% of CRP students had received treatment for a substance use disorder and most were in recovery less than 5 years. Student GPA improved in three of four CRPs. Colleges and CRPs need to engage in systematic data collection.